(3CWdS GdThGgO GdCKQjI Ydi eSGQGJ WQb GdbhGad GdbOjeI aj THg GdLRjQI GdYQHjI (B/s - (3GdTGjY, YHO Gddg Hf eMeO,s 1355 (3gLQj(B-s ((3GdQjGV (B:s (3OGQI Gdedc YHO GdYRjR,s, 2009)
(3jbOe GdcJGH eGFI hKeGf hCQHYjf UhQI dfeGPL hCfeGW ef GdUhQ hGdePjdGJ hGdOhGFQ GdMLQjI hZjQgG, hba YdjgG GdeDda CKfGA JJHYg deSGQGJ WQb GdbhGad GdbOjeI Vef QMdGJ ejOGfjI TedJ GdeedcI GdYQHjI GdSYhOjI, hGdeedcI GdCQOfjI GdgGTejI hSdWfI YeGf hGdjef ef NdGd eTQhY JMbjb eSGQGJ WQb GdbhGad GdbOjeI aj THg GdLRjQI GdYQHjI GdPj JMJVfg OGQI Gdedc YHO GdYRjR, ceG cGf dg hbaGJ YfO HYV gPg GdCTcGd hGdCfeGW GdMLQjI(B.s
(3jTJed Ydi cTGaGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B224-225.s
Keywords: (3GdCWGdS GdJGQjNjIs -- (3THg GdLRjQI GdYQHjIs; (3GdWQb GdJLGQjIs -- (3THg GdLRjQI GdYQHjIs -- (3JGQjNs; (3THg GdLRjQI GdYQHjIs -- (3LZQGajG JGQjNjIs; (3THg GdLRjQI GdYQHjIs -- (3BKGQs